EVALUASI MASTERPLAN PELABUHAN MAUMERE - , DEDI IMANUEL PAU, Prof. Ir. Nur Yuwono, Dip, HE., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maumere Port is located in the bay of Maumere, Flores Island and included in Sikka regency, East Nusa Tenggara Province. To further improve the service it is necessary to evaluate the masterplan of Maumere Port that made based on the data of 1996-2000 to the latest data is data from 2008-2012. It aims to determine the need for port space, equipment needs, predicted the development of ship visits and improved loading and unloading, port existing conditions based on SWOT analysis and make appropriate improvements to the existing master plan refer to the development of the flow vessel, cargo and passengers. This study uses trend projection based on historical data traffic growth and trends. Trend projection method used is regression analysis using excel software with respect to population and GDP growth from its hinterland. Predictions are made based on the latest data is data from 2008-2012, and then analyzed based on the projected traffic demand space port and harbor equipment for years to come. The results of this analysis are then used to evaluate the masterplan of Maumere Port. Based on the analysis the needs of container yard, predictable needs in 2014 amounted to 14.960 m2, 31.240 m2 of 2020 and 2025 amounted to 44.770 m2. Land in mainland DLKr Maumere Port that can be allocated as container yards amounted to 16,128.14 m2. Warehouse and open yard predicted could still accommodate the flow of containers through 2025. Passenger terminal building land predicted that there is still sufficient for building a broad but there must be added. Land parking area there is still sufficient. From the calculation of predicted equipment needs in 2014, container loading and unloading equipment required is 1 unit of shore cranes, 3 units of head truck and 3 units of mobile cranes. 2020 is 2 units of shore cranes, 4 unit of head truck and 3 units of mobile cranes. In 2025 is 2 units of shore crane, 5 unit of head truck and 4 units of mobile cranes. Based on the SWOT analysis can be known environmental factors that are internal and external strengths, weaknesses, opportunities and threats for the Port of Maumere, namely : port status, port geographic, financial resources, port services, ship waiting time, unloading time, local regulation and government regulation, growth hinterland, the port user participation, development of port technology, competition with the nearby port and socio-cultural factors.